EXPERIMENTAL STUDY OF THREAD TENSION IN THE PROCESS OF FORMING STITCH TYPE 101 - MANOILENKO, OLEKSANDR; BEZUHLYI, DMYTRO; HORIASHCHENKO, SERHIY; ROSTOVA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the problem of ensuring stable quality of the single-thread chain stitch type 101 when sewing materials of variable thickness, in particular multilayer packaging and sheet materials. The key factor that determines the structure and strength of the thread joint is the correspondence of the function of actual thread feed P(φ) to the required thread feed P′(φ). Any deviations between them directly affect the thread tension force and the quality of the formed stitch. For quantitative evaluation of this process, experimental studies were carried out on industrial machines of the GK-9 series using the ELTENS tensometric device. Measurements were performed at the minimum and maximum values of the technological parameters of the stitch (t = 8…14 mm, m = 0.4…8 mm). The obtained results made it possible to establish the regularities of thread tension change in different periods of stitch formation. It was shown that at the minimum parameters the maximum force is 1.28 N, while at the maximum parameters it reaches 6.2 N. Thus, with a twenty-fold increase in material thickness, the thread tension force at the moment of stitch tightening increases fivefold. Peak values are observed in the range φ = 270–360°, which corresponds to the stitch tightening period. Thus, the tension force can serve not only as a physical marker of the tightening moment, but also as an analytical criterion for checking the consistency of the thread feed model with changes in technological parameters, provided that the proper stitch quality is ensured. The results can be used to improve models of thread feed and to predict the magnitude of compression of multilayer materials during sewing.